Glossopharyngeal Nerve Block versus Lidocaine Spray to Improve Tolerance in Upper Gastrointestinal Endoscopy - Moisés Ortega Ramírez; Benigno Linares Segovia; Marco Antonio García Cuevas; Jorge Luis Sánchez Romero; Illich Botello Buenrostro; Norma Amador Licona; Juan Manuel Guízar Mendoza; Jesús Francisco Guerrero Romero; Víctor Manuel Vázquez Zárate (Gastroenterology Research and Practice)
Aim of the Study. To compare the effect of glossopharyngeal nerve block with topical anesthesia on the tolerance of patients to upper gastrointestinal endoscopy. Methods. We performed a clinical trial in one hundred patients undergoing upper gastrointestinal endoscopy. Subjects were randomly assigned to one of the following two groups: (1) treatment with bilateral glossopharyngeal nerve block (GFNB) and intravenous midazolam or (2) treatment with topical anesthetic (TASS) and intravenous midazolam. We evaluated sedation, tolerance to the procedure, hemodynamic stability, and adverse symptoms. Results. We studied 46 men and 54 women, from 17 to 78 years of age. The procedure was reported without discomfort in 48 patients (88%) in the GFNB group and 32 (64%) in the TAAS group; 6 patients (12%) in GFNB group and 18 (36%) in TAAS group reported the procedure as little discomfort (χ2=3.95, P=0.04). There was no difference in frequency of nausea (4% in both groups) and retching, 4% versus 8% for GFNB and TASS group, respectively (P=0.55). Conclusions. The use of glossopharyngeal nerve block provides greater comfort and tolerance to the patient undergoing upper gastrointestinal endoscopy. It also reduces the need for sedation.